Cross-cultural adaptation and validation of the Romanian International Knee Documentation Committee—subjective knee form - Adrian Todor; Dinu Vermesan; Horia Haragus; Jenel M. Patrascu Jr; Bogdan Timar; Dan I. Cosma (PeerJ, 2020)
Aim We aimed to translate and cross-culturally adapt the International Knee Documentation Committee—subjective knee form (IKDC) in Romanian. Method The original (US) IKDC—subjective knee form was translated according to recommended guidelines. Validity was tested using Spearmans’s correlation coefficient between score sand test-retest reproducibility. Reliability and internal consistency were determined using Cronbach’s alpha coefficient and intraclass correlation coefficient (ICC). Results A total of 106 data sets were available for processing. The average age was 52 years and the male to female ratio was 40:66. Fifty-five subjects repeated the form after an average of 4 days. There were no floor or ceiling effects (range 3.4–74.7). There was a strong correlation between the first and repeated administration of the IKDC—subjective knee form (r = 0.816, n = 50) and moderate compared to Tegner-Lysholm knee rating scale (r = 0.506, n = 102), KOOSJR (Knee disability and Osteoarthritis Outcome Score for Joint Replacement, r =  − 0.622, n = 96), EuroqolEQ-5D-5L Index (r = 0.633, n = 100) and visual analogue scale VAS (r = 0.484, n = 99). Internal consistency was moderate with Cronbach’s alpha 0.611 (n = 102) and ICC 0.611 for average measures (95% CI 0.493–0.713). Conclusion The Romanian translation of the IKDC—subjective knee form is a valid, consistent and reproducible outcome measure in patients with knee pain and dysfunction.